2012
DOI: 10.5137/1019-5149.jtn.5989-12.1
|View full text |Cite
|
Sign up to set email alerts
|

Rathke’s cleft cyst with non-hemorrhagic rupture resulting in alteration of signal intensity for a short period: case report.

Abstract: In a case of 23-year-old female with Rathke's cleft cyst (RCC), unusual changes with size and morphology on computed tomography (CT) and magnetic resonance images (MRI) were noted in a short period of 3 weeks after spontaneous rupture. The CT noted that the intracystic isodensity was changed to hyperdensity. And MRI showed not only a decrease in size of the lesion but also changing from hypo-and hyperintensity in T1-and T2-weighted images to hyperintensity in both T1-and T2-weighted images. The intraoperative … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Since that time, numerous additional case reports of XG have suggested that, when an etiology can be identified at all, it is a hemorrhagic RCC that is implicated. In addition, since the report of Paulus et al , numerous examples of hemorrhagic and non‐hemorrhagic RCCs mimicking pituitary apoplexy have been published, underscoring the fact that bleeding into RCC may be both subclinical and clinically relevant . The etiological mechanism behind hemorrhage into RCCs is obscure, but usually there is no identified antecedent traumatic or other inciting event.…”
Section: Introductionmentioning
confidence: 99%
“…Since that time, numerous additional case reports of XG have suggested that, when an etiology can be identified at all, it is a hemorrhagic RCC that is implicated. In addition, since the report of Paulus et al , numerous examples of hemorrhagic and non‐hemorrhagic RCCs mimicking pituitary apoplexy have been published, underscoring the fact that bleeding into RCC may be both subclinical and clinically relevant . The etiological mechanism behind hemorrhage into RCCs is obscure, but usually there is no identified antecedent traumatic or other inciting event.…”
Section: Introductionmentioning
confidence: 99%